Nation of compassion in Islam - Fatah Yasin, Raudlotul Firdaus (Office of Sultan Haji Ahmad Shah Mosque, IIUM, 2017)
Nation of compassion refers to the group of communities who continuously put their effort to implement mercy and love in all aspects of lives, which lead the society to live in harmony, peace, justice and respect.”